TLR7 agonist administration to SIV-infected macaques receiving early initiated cART does not induce plasma viremia - Del Prete, Gregory Q. (JCI Insight, 2019)
Reduction/elimination of HIV-1 reservoirs that persist despite combination antiretroviral therapy (cART) will likely require induction of viral expression by residual infected cells and enhanced clearance of these cells. TLR7 agonists have potential to mediate these activities. We evaluated immunologic and virologic effects of repeated doses of the TLR7 agonist GS-9620 in SIV-infected rhesus macaques receiving cART, which was initiated at 13 days after infection and was continued for 75 weeks prior to GS-9620 administration. During cART, GS-9620 induced transient upregulation of IFN-stimulated genes in blood and tissues, increases in plasma cytokines, and changes in immune cell population activation and phenotypes but did not result in measurable increases in plasma viremia or viral RNA–to–viral DNA ratio in PBMCs or tissues nor decreases in viral DNA in PBMC or tissues. SIV-specific CD8(+) T cell responses, negligible prior to GS-9620 treatment, were not measurably boosted by treatment; a second course of GS-9620 administration overlapping with later cART discontinuation was associated with increased CD8(+) T cell responses during viral recrudescence. These results confirm and extend evidence for GS-9620–mediated enhancement of antiviral immune responses in SIV-infected macaques but suggest that GS-9620–mediated viral induction may depend critically on the timing of initiation and duration of cART and resulting characteristics of viral reservoirs.